Social Class Differentiation and Its Impact on Quality of Life Among Diabetic Patients - Rohin Rameswarapu; Trupti N Bodhare; Samir D Bele; Sameer Valsangkar (Medsci Publications, 2011)
Social class is a significant modifier of quality of life in diabetic patients which we sought to measure in this study. A hospital based, cross sectional descriptive was conducted in diabetic patients using a semi structured questionnaire. A total of 103 diabetic patients consented and participated in the study. The sample consisted of 58 males and 45 females and most respondents had a duration of onset of diabetes between 1-5 years (47%). 68 (66%) of the respondents belonged to lower class, 27 (26%) to the middle class and 8 (8%) to the upper class. 92 (89.32%) of the respondents were using oral hypoglycemic agents and 11 (10.68%) used injectable insulin. Socioeconomic status was significant for the number of missed doses (P < 0.04). The mean scores for upper, middle and lower class on the items of financial burden were 3.99 ± 0.906, 3.37 ± 1.079, 3.00 ± 0.756, for general health were 3.49 ± 0.837, 2.96 ± 0.706, 2.63 ± 0.744 and for psychological distress were 3.56 ± 0.835, 2.70 ± 0.609 and 2.75 ± 0.707 respectively. Social class has a significant impact on quality of life and therapy compliance and measures to address this must be undertaken while providing comprehensive healthcare in diabetes for an optimal outcome.